Performance of Subcarrier and Power Allocation Orthogonal Frequency-Division Multiplexing on Millimeter Wave - Naemah Mubarakah; Rika Wahyuni Arsianti; Mulyadi Mulyadi (Universitas Ahmad Dahlan, 2013)
Local multipoint distribution system (LMDS) that operated in millimeter waves can be used to fulfill the need of bit rate higher than 40 Mbps. However it has problem when applied in tropic country such as Indonesia because of the high rainfall. Therefore LMDS system was developed by cross-layer mechanism. In this research we used joint subcarrier and power allocation (JSPA) technique in multi-user cross-layer OFDM. This technique is proposed to increase the performance of telecommunication system even there were disturbance of rain attenuation. The research is discussing the performance of transmission capacity, data rate, utility and fairness of JSPA algorithm that applied in rain attenuation measurement in Surabaya. The result shows the increment of performance system using JSPA technique. For 40 dB rain attenuation, JSPA can achieves respectively average capacity of transmission up to 173,3%, 189,9 % for data rate and 9,6% for fairness system. The application of JSPA technique improve the performance of utility 13,61-15,48 bps/Hz